Migrants; Refugees; and Displaced in the Middle East and North Africa: An approach from the Global South: An approach from the Global South - Gonçalves, Maria do Carmo dos Santos (2022)
This article aims to introduce aspects involved in studies on migratory dynamics in the Middle East and North Africa (MENA). In this sense, we present some historical dynamics for defining the territories of what is considered the MENA region, as well as highlighting the participation of these countries in the context of the migratory and humanitarian crises that have characterized the dynamics of mobility in and in the region. In such a context, we draw attention to the politicization of migratory phenomena and to the still sparse study and research initiatives that analyze the migratory dynamics of countries in the MENA region to the global south. Finally, the article introduces the discussions on migrations in the MENA region that are part of this dossier, inviting the reader to dialogue with different theoretical-methodological approaches on the migration phenomenon in that context.